The Fault Lines of Modernity: A Mixed-Methods Autopsy of State Power, Social Resistance, and Identity Dialectics in Indonesia's New Capital Project - Amir Serikova; Henry Clifford; Muhammad Faiz (Open Access Indonesia Journal of Social Sciences, 2025)
The state-led relocation of Indonesia's capital to Nusantara (IKN) is a monumental project framed as a leap into a sustainable future. However, this top-down imposition of modernity is creating deep social fissures on the ground. This study conducts a sociological autopsy of the IKN development, dissecting the intricate mechanisms of resistance, displacement, and identity formation among affected communities. We employed a concurrent embedded mixed-methods design in North Penajam Paser, East Kalimantan (Jan 2024–Mar 2025). A structured survey was administered to 500 households, selected via a multi-stage sampling process, to quantify displacement anxieties and resistance participation. This was triangulated with 50 in-depth interviews with community leaders, displaced residents, and officials. Quantitative data were analyzed using t-tests and a Negative Binomial regression model to identify predictors of resistance, while qualitative data were analyzed thematically. Survey data revealed profound anxiety, with indigenous communities reporting significantly higher distress levels (t(498) = 10.2, p < 0.001). The Negative Binomial regression identified indigenous status (IRR=3.45, p<0.001), reliance on agro-forestry (IRR=2.88, p<0.001), and higher anxiety scores (IRR=1.12, p<0.001) as significant predictors of increased participation in resistance activities. Qualitative findings uncovered a sophisticated "tripartite arsenal" of resistance (symbolic, material, legal) and documented the emergence of a "Janus-faced" state, perceived as both coercively present and procedurally absent. In conclusion, the IKN project is a site of intense social struggle where competing modernities collide. State-led development, without genuine participation, engenders resilient and adaptive forms of social resistance and catalyzes a dialectical process of identity politicization. We argue that IKN risks becoming a landscape of exclusionary modernity unless a fundamental shift towards rights-based development is enacted.